Superior reinforcement of ethyl-co-vinyl acetate rubber composites by using nano-sized starch filler: The role of particle size and reactive compatibilization. (August 2018) - Xu, Pengwu; Zhao, Xiyuan; Niu, Deyu; Hoch, Martin; Ma, Piming; Dong, Weifu; Chen, Mingqing; Deshmukh, Yogesh
Graphical abstract: Highlights: Starch was designed as active filler by a suitable chemical compatibilization. Ts of EVM was increased by 5.4 times with NSt and chemical compatibilization. It provides a new approach to design multi-network and strong interfacial bonding. New application of natural starch was developed in general in rubber technology. Abstract: Nano-sized starch (NSt) was reported as reactive filler to reinforce ethylene-co-vinyl acetate rubber (EVM) by using epoxy-functionalized EVM (GMA-EVM) as compatibilizer together with 3-(2-aminoethylamino) propyl dimethoxy methyl silane (KH602). This resulted in EVM/GMA-EVM/NSt nanocomposites having significant improved properties. The improvement is attributed to the small starch particle size and chemical compatibilization. The tensile strength ( Ts ) was increased from 9.2 to 18.7 MPa when 20 phr (per hundred rubber by weight) of the GMA-EVM compatibilizer is incorporated. Compared to EVM/NSt, the EVM/GMA-EVM/NSt nanocomposites possess stronger interfacial interaction between fillers and the matrix according to morphology and crosslink density analysis. Besides the crosslink of EVM and GMA-EVM chains created by dicumyl peroxide (DCP), under the aid of KH602, extra chemical bonding was generated between: (a) GMA-EVM chains, (b) GMA-EVM and NSt. Thus, strong reinforcement of EVM was obtained. These interesting results provide a new insight to make robust rubbers which may create new applications for rubbers and natural fillers.